(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: (1) To investigate the prevalence of positive HBsAg test results; (2) To describe hepatitis B virus (HBV) serological profiles using the three-test panel of HBsAg, anti-HBs, and total anti-HBc at Vinmec Times City International General Hospital in 2024. Materials and methods:A cross-sectional descriptive study was conducted on 45,433 serum/plasma samples tested for HBsAg, anti-HBs, and total anti-HBc using the automated immunoassay system Cobas e801 at Vinmec Times City International General Hospital (VMTC) in 2024. Retrospective data on age, sex, and test results of HBsAg, anti-HBs, and total anti-HBc were collected at VMTC. Results:Among 45,433 samples, the prevalence of HBsAg positivity was 5.87%. Males had a significantly higher prevalence (7.32%) than females (4.71%). The lowest prevalence was observed in individuals under 18 years of age (0.43%), while the highest was found in those aged over 46 years (up to 7.53%). Among 30,206 HBsAg-negative, 43.64% lacked protective immunity (anti-HBs <10 IU/mL). A total of 2,265 individuals (4.99%) underwent the complete three-test panel of HBsAg, anti-HBs, and total anti-HBc; based on this panel, 7.59% were identified as having chronic HBV infection, and 39.96% had evidence of past exposure with recovery. Conclusions: The prevalence of HBsAg positivity in this study was 5.87%, with higher rates observed in males and in individuals aged ≥46 years compared with other groups. The proportion of samples tested with the complete three-test HBV serological panel was 4.99%, among which 7.59% had chronic HBV infection and 39.96% showed evidence of past exposure and recovery.